Opsis: the visuality of Greek drama - Meineck, Peter (2011)
How were Greek plays viewed in the fifth century BCE and by deepening our understanding of their visual dimension might we increase our knowledge of the plays themselves? The aim of this study is to set out the importance of the visual (opsis) when considering ancient Greek drama and provide a basis for constructing a form of “visual dramaturgy” that can be effectively applied to the texts. To that end, this work is divided into five sections, which follow a “top-down” analysis of ancient dramatic visuality. The analysis begins with a survey of the prevailing visual culture and Greek attitudes about sight and the eye. Following this is an examination of the roots of drama in the performance of public collective movement forms (what I have called “symporeia”) and their relationships to the environments they moved through, including the development of the fifth century theatre at the Sanctuary of Dionysos Eleuthereus in Athens. The focus then falls on the dramatic mask and it is proposed here that operating in this environment it was the visual focus of Greek drama and the primary conveyer of the emotional content of the plays. Drawing on new research from the fields of cognitive psychology and neuroscience relating to facial processing and recognition, gaze direction, foveal and peripheral vision and neural responses to masks, movement and performance, it is explained how the fixed dramatic mask was an incredibly effective communicator of dramatic emotion capable of eliciting intensely individual responses from its spectators. This study concludes with a case study based on Aeschylus Oresteia and the raising of Phidias’ colossal bronze statue of Athena on the Acropolis and the impact that this may have had on the original reception of the trilogy.